2017
DOI: 10.1002/aoc.3857
|View full text |Cite
|
Sign up to set email alerts
|

Intensified removal of Malachite green by AgOH‐AC nanoparticles combined with ultrasound: Modeling and optimization

Abstract: In this work Random Forest (RF) and Response surface methodology (RSM) were used to model and predict the efficiency of malachite green removal from aqueous solution by ultrasound-assisted adsorption onto the silver hydroxide nanoparticles loaded on activated carbon (AgOH-NPs-AC). The prepared nanoparticles were characterized by SEM, FTIR, XRD and TEM. The parameters such as pH, initial MG concentration, sonication time and adsorbent dosage involved in the adsorption process were set within the ranges 2.0-10, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(8 citation statements)
references
References 35 publications
(37 reference statements)
0
8
0
Order By: Relevance
“…The Garson method for calculating the influence of each input variable on the output variable using weight and bias is shown in Table 5. The high importance score of variables indicates that the contribution of variables is significant to dye removal prediction [83]. Table 6 gives the factor importance obtained from F value, Garson method, GBRT and RF, which shows that the dosage had the maximum importance to the EV removal by Mn-doped Fe/rGO.…”
Section: Comparison Among Analysis Of Variance Gbrt Garson Methods Amentioning
confidence: 99%
“…The Garson method for calculating the influence of each input variable on the output variable using weight and bias is shown in Table 5. The high importance score of variables indicates that the contribution of variables is significant to dye removal prediction [83]. Table 6 gives the factor importance obtained from F value, Garson method, GBRT and RF, which shows that the dosage had the maximum importance to the EV removal by Mn-doped Fe/rGO.…”
Section: Comparison Among Analysis Of Variance Gbrt Garson Methods Amentioning
confidence: 99%
“…More recently, our group simplified their MLR model by introducing only four inputs, namely, pH, sonication time, adsorbent dose, and the initial dye concentration. Their results indicated that the proposed method cannot well predict the removal dye percentage [13,[30][31][32][33][34][35].…”
Section: Multiple Linear Regressionmentioning
confidence: 99%
“…In another work by our group [13], random forest (RF) and response surface methodology (RSM) were used to model and predict the efficiency of malachite green removal from aqueous solution by ultrasound-assisted adsorption onto the silver hydroxide nanoparticles loaded on activated carbon (AgOH-NPs-AC). The parameters such as pH, initial MG concentration, sonication time, and adsorbent dosage involved in the adsorption process were set within the ranges 2.0-10, 4-20 mg L −1 , 2-6 min, and 0.005-0.025 g, respectively.…”
Section: Ensemble Prediction Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…RSM is generally unable to give a suitable model due to the fact that the relation between effective parameters and removal of dye is too complicated and difficult to model by regression analysis. However, recently RSM and nonlinear methods such as support vector machine, random forest, tree regression and decomposition algorithm have been used jointly to solve this issue and for modelling or/and optimization in environmental studies . However, there has been little study of modelling dye removal using RSM and intelligent systems.…”
Section: Introductionmentioning
confidence: 99%